2011
DOI: 10.1089/ten.teb.2011.0235
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Pore Size of Electrospun Scaffolds

Abstract: Electrospinning has gained much attention in the past decade as an effective means of generating nano- to micro-scale polymer fibers that resemble native extracellular matrix. High porosity, pore interconnectivity, and large surface area to volume ratio of electrospun scaffolds make them highly conducive to cellular adhesion and growth. However, inherently small pores of electrospun scaffolds do not promote adequate cellular infiltration and tissue ingrowth. Cellular infiltration into the scaffold is essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
186
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(190 citation statements)
references
References 57 publications
4
186
0
Order By: Relevance
“…Figure 4 clearly demonstrated that sulphur mutated simulant chemical molecules is adhered onto surface of the web and therefore, web is acting as a barrier layer for CWA sulphur mustard gas. On the other hand, air permeability, water vapour, and bacteria and chemical filtration results of functional integrated layer showed agreement and correlation with those obtained by pore size and morphological measurements [24][25][26][27][28][29][30][31]. Nanoweb morphology act as a barrier layer is in close agreement with previously reported work for various other applications [32][33][34][35][36][37][38][39].…”
Section: Figure 2 Fesem Images Of Acs Adhered Woven Fabric Of Differsupporting
confidence: 88%
“…Figure 4 clearly demonstrated that sulphur mutated simulant chemical molecules is adhered onto surface of the web and therefore, web is acting as a barrier layer for CWA sulphur mustard gas. On the other hand, air permeability, water vapour, and bacteria and chemical filtration results of functional integrated layer showed agreement and correlation with those obtained by pore size and morphological measurements [24][25][26][27][28][29][30][31]. Nanoweb morphology act as a barrier layer is in close agreement with previously reported work for various other applications [32][33][34][35][36][37][38][39].…”
Section: Figure 2 Fesem Images Of Acs Adhered Woven Fabric Of Differsupporting
confidence: 88%
“…Most tissue engineering applications demand 3D-structured scaffolds with open pores to enable cell infiltration. Different strategies such as special collectors 17 and salt leaching 18 were used to enhance the pore size and thickness of nanofibrous layers. Currently, alternative methods to prepare nano-and microfibers, such as melt-blown or centrifugal spinning, are being tested for tissue engineering applications.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Moreover, the resulting scaffolds lack the possibility to add scalable pores and often show poor mechanical stability. [8] Recently, Ding and Greiner pioneered a simple way of producing ultralight nanofiber based aerogels or sponges by cutting electrospun membranes into short fiber fragments and subsequently freeze-drying the slurry of these fragments. [2a,b] The idea of using short electrospun nanofibers to enhance the mechanical stability of composites was already proposed by Reneker.…”
Section: Introductionmentioning
confidence: 99%